2020
DOI: 10.1515/tjb-2020-0410
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte-to-C-reactive protein ratio may serve as an effective biomarker to determine COVID-19 disease severity

Abstract: Objectives We aimed to evaluate the ability of lymphocyte-C-reactive protein ratio (LCR) to discriminate between different levels of severity of COVID-19 disease. Methods This retrospective observational single-center study was performed on 61 confirmed (PCR positive) COVID-19 patients between March and June 2020. The study population was separated into three groups: mild/moderate (n=24), severe (n=25) and critically ill (n=1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 25 publications
1
16
1
Order By: Relevance
“…While a high lymphocyte:CRP ratio has also been proposed as an adverse prognostic factor in COVID-19, the non-specific nature of CRP may affect the routine applicability of this parameter. 45 …”
Section: Discussionmentioning
confidence: 99%
“…While a high lymphocyte:CRP ratio has also been proposed as an adverse prognostic factor in COVID-19, the non-specific nature of CRP may affect the routine applicability of this parameter. 45 …”
Section: Discussionmentioning
confidence: 99%
“…Elevated CRP level is also observed in patients having COVID-19 (Aktas, 2021). Studies have shown that the correlation of lymphocyte/CRP ratio with clinical severity is superior to NLR in COVID-19 patients (Bal et al, 2021;Lagunas-Rangel, 2020). Similar to CRP, elevated D-dimer value is a typical phenomenon in patients with COVID-19 (Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 94%
“…The prognostic and diagnostic association of these parameters with COVID-19 remains unclear (Bal et al, 2021;ElshazliI et al, 2020). The present study compared the lymphocyte/CRP ratio (LCR), NLR, neutrophil count, MPV, PLT, neutrophil, CRP, and D-dimer values in patients with COVID-19 and a non-COVID-19 control group.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although previous studies have shown that most patients with COVID-19 (nearly 80%) have initially mild or moderate disease and a favorable clinical outcome, others experience severe or critical illness. 2 Early diagnosis of these patients is crucial to decrease admissions to the intensive care unit (ICU) as well as the length of hospitalization, mortality rate, and hospital costs. 3 , 4 Cytotoxicity caused by the causative agent, SARS-CoV-2, in pulmonary endothelial cells and the consequences of severe inflammatory outcomes can cause serious and even life-threatening illness.…”
Section: Introductionmentioning
confidence: 99%